Dialogical Exposure with Traumatically Bereaved Bosnian Women: Findings from a Controlled Trial. (24th September 2014) - Hagl, Maria; Powell, Steve; Rosner, Rita; Butollo, Willi
Abstract : Objective: In this trial, we compared the relative efficacy of dialogical exposure group treatment using Gestalt empty‐chair method with a supportive group in the treatment of symptoms stemming from traumatic loss in a post‐war society. Methods: One‐hundred and nineteen women whose husbands were either killed or registered as missing during the war in Bosnia and Herzegovina were quasi‐randomized to seven sessions of group treatment with dialogical exposure or to an active control condition. Results: Both interventions resulted in significant improvement from baseline to post‐treatment for both kinds of loss, in terms of post‐traumatic symptoms, general mental health and grief reactions, with the exception of depression and traumatic grief in the control condition. Regarding mean effect sizes (Cohen's d ), pre‐treatment to post‐treatment improvements were moderate ( d = 0.56) for the dialogical exposure group and small ( d = 0.34) for the supportive group. Treatment gains were maintained at least until the 1‐year follow‐up. In controlled comparisons, dialogical exposure was superior concerning traumatic grief (Cohen's d = 0.37) and post‐traumatic avoidance ( d = 0.73) at post‐treatment. Conclusions: Results show that short‐term dialogical exposure group treatment was moderately effective in treating traumatically bereaved women. Copyright © 2014 John Wiley & Sons, Ltd. Key Practitioner Message: Research attests to high levels of symptoms among post‐war civil populations, in particular, when a loved one was killed, which can lead not only to trauma reactions but also to severe separation distress. Grieving the loss of a loved one is hampered if the death remains unconfirmed. Unconfirmed loss could be conceptualized as unfinished business in terms of Gestalt therapy, which offers empty‐chair dialogue for resolving unfinished business and grief. Dialogical exposure therapy (DET) supports the client in gaining awareness of and expressing his or her inner dialogues concerning the traumatic event, using Gestalt empty‐chair method. Short‐term DET was effective in treating traumatically bereaved women but showed little additional effects in comparison with a supportive group treatment, so further research is warranted.